Prach alebo popol Kremácia v židovskej komunite na Slovensku z pohľadu etnológie - Salner, Peter (Ethnological studies, 2023)
Title: Dust or ashes: Cremation in the Jewish community in Slovakia from the perspective of ethnology. Traditional Judaism accepts only the burial of remains in the ground and fundamentally rejects cremation. Nevertheless, in recent decades, Jewish community members have increasingly preferred burial in a crematorium. In the last decade, cremation has been the majority form of burial. Based on long-term archival and ethnological research, Peter Salner analyzes the causes and consequences of the spread of this religiously forbidden and practically unknown trend in the past. The author notes that in most cases, cremation is not a sign of an effort to hide or reject Jewish identity. He interprets this burial method as the result of a change in values after the Holocaust and during the period of communist rule. As one of the proofs, he cites the wish of the members of the community to be able to place the urns of their loved ones on Jewish land. The result of these efforts is the fact that the leadership of the Jewish Religious Community approved the construction of a columbarium on the premises of the Neological Cemetery in Bratislava after lengthy discussions in 2007. Based on the findings, the author concluded that the spread of cremation represents a form of post-Holocaust non-religious Jewish identity.